Pengembangan Modul Digital Berbasis Web pada Elemen Menggambar Mode di SMK YPM 2 Taman - Faizah Salsabila Ahmady; Imami Arum Tri Rahayu (Departement of Mathematics Education, 2023)
The Ministry of Education, Culture, Research & Technology issued a curriculum development policy for education units to be implemented in 2022, which is called the independent curriculum. This change is still gradual in class X so the teacher also has to adjust the learning process more effectively. This study aims to develop a web-based module on drawing elements mode sub-matter of color analysis in design in class X SMK YPM 2 Taman. The research development method used is Sugiyono's Research and Development only up to the validation stage. Research data was collected through observation and interview methods. The instrument used uses the method of analysis. The data analysis technique uses descriptive qualitative with the calculation of the Likert scale formula. The results of the validation research from the material validator and media validator stated that the percentages were 81.74% and 81.74% with very valid criteria. Based on the analysis of the data studied, it was concluded that the development of web-based digital modules on the elements of drawing mode is said to be feasible and can be applied to the learning process of students in class X SMK YPM 2 Taman.